Gail R. Martin (1944–2026): Embryonic stem cell pioneer, developmental biologist, and student of Asian art and ceramics - Terry Magnuson; Thomas Kornberg (Proceedings of the National Academy of Sciences, 2026)
Gail Roberta Martin, Professor Emerita of Anatomy at the University of California, San Francisco, and one of the founding figures of modern stem cell and developmental biology, passed away on February 9, 2026. A memorial service celebrating her life was held on February 22, 2026, at the Julia Morgan Chapel at the Chapel of the Chimes in Oakland, a building designed by one of the twentieth century’s great pioneering female architects, and a fitting setting for a scientist who broke barriers of her own. Gail is remembered by her colleagues, students, and friends as a scientist of rare originality and intellectual courage, a generous mentor, and a deeply curious person whose love of learning never diminished.